2020
DOI: 10.3332/ecancer.2020.1035
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in women affected by gynaecological cancer: the importance of an integrated gynaecological and psychological approach

Abstract: Gynaecological cancer treatment significantly affects the fertility of women in reproductive age. Surgery, chemotherapy and radiotherapy are the mainstays of ovarian, cervical and endometrial cancers and anatomically or functionally impact the uterus and ovaries. Moreover, the sexual function and psychological wellbeing of patients are highly weakened after a cancer diagnosis: depression, anxiety and impairment of quality of life represent a relevant concern for patient care. The potential loss of fertility co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 64 publications
0
37
0
4
Order By: Relevance
“… 30 The possible loss of fertility during treatment with cancer can be more distressing than cancer itself, according to recent reports where efforts to maintain fertility through techniques such as fertility-sparing surgery are essential in younger women diagnosed with gynecological cancers as they could lead to an improvement in quality of life. 31 Another recent study indicated high levels of psychological distress when diagnosed women reach childbearing age as menstrual function and fertility were lost. It is therefore important to monitor the progression of cancer but should also provide appropriate fertility preservation counselling.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The possible loss of fertility during treatment with cancer can be more distressing than cancer itself, according to recent reports where efforts to maintain fertility through techniques such as fertility-sparing surgery are essential in younger women diagnosed with gynecological cancers as they could lead to an improvement in quality of life. 31 Another recent study indicated high levels of psychological distress when diagnosed women reach childbearing age as menstrual function and fertility were lost. It is therefore important to monitor the progression of cancer but should also provide appropriate fertility preservation counselling.…”
Section: Discussionmentioning
confidence: 99%
“…In a fertility sparing approach, a multidisciplinary team, including a psychological support for the woman, is essential. Anxiety, depression and fear could harass the patient during the therapeutic path; enhancing her quality of life through a psychological support is crucial in order to improve the efficacy of the treatment (85)(86)(87).…”
Section: First Histological Sample Second Histological Sample Third Histological Sample Initial Assessmentmentioning
confidence: 99%
“…Early diagnosis of ovarian cancer through relevant basic research will maximize fertility preservation. This will significantly reduce the impact on sexual function, mental health, quality of life, and other aspects [ 1 ].…”
Section: Introductionmentioning
confidence: 99%